Provincial level estimation of selected health indicators prevalence among children under five years old in the Philippines - Ong, Jovin David C.; Asaad, Abubakar S.; Sy, Alvin Duke R.; Pinlac, Paul Adrian V.; Climacosa, Fresthel Monica M.; Cruz, Eduardo (Manila College of Public Health, University of the Philippines Manila, 2025)
A fundamental aspect of public health is the well-being of children, which significantly influencing population health outcomes on a global scale. In low- and middle-income countries, common childhood illnesses contribute to higher rates of morbidity and mortality, resulting in increased healthcare utilization and expenditure. This study aims to estimate the provincial level prevalence, defined by the Demographic and Health Surveys (DHS) program as the proportion of a population found to have a particular condition at a given point in time, of diarrhea, fever, and acute respiratory infections (ARIs) among children under five in the Philippines, addressing the significant health burdens these conditions pose. Utilizing data from the 2017 and 2022 National Demographic and Health Survey (NDHS), this study employed small area estimation (SAE) methods such as direct estimation and nearest neighbor methods to derive reliable prevalence for these health indicators. The significance of this research lies in its contribution to public health data, providing essential estimates that can inform resource allocation, identify health inequities, and evaluate the effectiveness of current health programs. The findings revealed varying prevalences across provinces, highlighting disparities that necessitate targeted public health interventions. Specifically, direct estimation provided a baseline prevalence, while the time-space and geographical nearest neighbor methods offered enhanced provincial insights. The results underscore the urgent need for tailored health strategies to address the high prevalence of diarrhea, fever, and ARI in vulnerable populations, particularly children under five. In conclusion, the study recommends the integration of reliable provincial health indicator estimates into health policies and programs, as well as the implementation of targeted interventions aimed at reducing childhood morbidity. Furthermore, it advocates for strengthened data collection and surveillance systems in provinces with small or sparse populations to fill knowledge gaps regarding these critical health issues, aligning with national and global development agenda. By leveraging accurate data, health authorities can better strategize to improve child health outcomes across the provinces.
Includes references and appendices.
Thesis
Keywords: Child health -- Statistics. -- Philippines .; Health surveys -- Statistical methods. -- Philippines .; Children -- Health and hygiene -- Philippines -- Statistical methods